Prognostic value of aerobic capacity and exercise oxygen pulse in postaortic dissection patients. Issue 2 (31st December 2020) - Delsart, Pascal; Delahaye, Camille; Devos, Patrick; Domanski, Olivia; Azzaoui, Richard; Sobocinski, Jonathan; Juthier, Francis; Vincentelli, Andre; Rousse, Natacha; Mugnier, Agnes; Soquet, Jerome; Loobuyck, Valentin; et al.
Abstract: Background: Although recommendations encourage daily moderate activities in post aortic dissection, very little data exists regarding cardiopulmonary exercise testing (CPET) to personalize those patient's physical rehabilitation and assess their cardiovascular prognosis. Design: We aimed at testing the prognostic insight of CPET regarding aortic and cardiovascular events by exploring a prospective cohort of patients followed‐up after acute aortic dissection. Methods: Patients referred to our department after an acute (type A or B) aortic dissection were prospectively included in a cohort between September 2012 and October 2017. CPET was performed once optimal blood pressure control was obtained. Clinical follow‐up was done after CPET for new aortic event and major cardio‐vascular events (MCE) not directly related to the aorta. Results: Among the 165 patients who underwent CPET, no adverse event was observed during exercise testing. Peak oxygen pulse was 1.46(1.22‐1.84) mlO2/beat, that is, 97 (83–113) % of its predicted value, suggesting cardiac exercise limitation in a population under beta blockers (92% of the population). During a follow‐up of 39(20‐51) months from CPET, 42 aortic event recurrences and 22 MCE not related to aorta occurred. Low peak oxygen pulse (<85% of predicted value) was independently predictive of aortic event recurrence, while low peak oxygen uptake (<70% of predicted value) was an independent predictor of MCE occurrence. Conclusion: CPET is safe in postaortic dissection patients should be used to not only to personalize exercise rehabilitation, but also to identify those patients with the highest risk for new aortic events and MCE not directly related to aorta.